Verbal Magic in the Oral History from Lubelszczyzna Region – a Positive Aspect - Wójtowicz, Magdalena (Poznańskie Studia Slawistyczne, 2012)
The aim of this article is to give an anthropological description of verbal magic. The magical utterances are present in the following areas of traditional culture: folk medicine, family and annual rituals. They focus on a formula which, in the opinion of people expressing them, have some magical powers which cause positive effects in the real world. The empirical material, which constitutes the basis for the description, derives from the questionnaire interviews with inhabitants of the rural communities of Lublin voivodeship. The author focuses on the elements that must be satisfied that the words gained causative power. These elements are situational context (which includes time and place of activity, sender, recipient, symbolic attributes), repeating, fidelity playback, optional confidentiality.